2016
DOI: 10.1074/jbc.m115.703256
|View full text |Cite
|
Sign up to set email alerts
|

A Complex of Htm1 and the Oxidoreductase Pdi1 Accelerates Degradation of Misfolded Glycoproteins

Abstract: A quality control system in the endoplasmic reticulum (ER) efficiently discriminates polypeptides that are in the process of productive folding from conformers that are trapped in an aberrant state. Only the latter are transported into the cytoplasm and degraded in a process termed ER-associated protein degradation (ERAD). In the ER, an enzymatic cascade generates a specific N-glycan structure of seven mannosyl and two N-acetylglucosamine residues (Man7GlcNAc2) on misfolded glycoproteins to facilitate their di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
35
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 59 publications
0
35
1
Order By: Relevance
“…Finally, we made a second Htm1 mutant with a truncation of the amino acyl region from residue 572 to residue 657 (Δ572-657), which covers the region necessary for interaction with Pdi1p ( Fig. S2A) (14,23,28). Immunoprecipitation confirmed that Δ572-657 showed little detectable interaction with Pdi1p ( Fig.…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations
“…Finally, we made a second Htm1 mutant with a truncation of the amino acyl region from residue 572 to residue 657 (Δ572-657), which covers the region necessary for interaction with Pdi1p ( Fig. S2A) (14,23,28). Immunoprecipitation confirmed that Δ572-657 showed little detectable interaction with Pdi1p ( Fig.…”
Section: Resultsmentioning
confidence: 86%
“…To this point, our findings support two potential models describing how Htm1p-Pdi1p generates the α1,6-linked mannose signal for ERAD-L commitment. In one model, the catalysis by Htm1p-Pdi1p may be intrinsically slow and stochastic, as previously suggested (15,23), and unfolding facilitates demannosylation by increasing access to the glycan. Alternatively, Htm1p-Pdi1p may preferentially target specific folding states of nonnative proteins, and the aggregation-prone nature of misfolded CPY variants prevents them from populating in these states in vitro.…”
Section: Htm1p-pdi1p Preferentially Demannosylates Partially Structuredmentioning
confidence: 93%
See 2 more Smart Citations
“…Although A1AT NHK -GFP and GFP-RTA E177Q share a strict dependence on the core membraneintegrated HRD1/SEL1L complex and its associated cytosolic components, they differ strikingly in their dependence on N-glycosylation. A1AT NHK -GFP degradation was strongly dependent on the mannosidase complex composed of EDEM2/3 and the oxidoreductases TXNDC11 and PDI that generates the mannose-trimmed Asn-linked glycan which marks proteins for destruction (Clerc et al, 2009;Gauss et al, 2011;Molinari et al, 2003;Ninagawa et al, 2014;Oda et al, 2003;Pfeiffer et al, 2016;Timms et al, 2016), and the lectin, OS9, that recognizes this glycan signal and delivers proteins to HRD1/SEL1L (Christianson et al, 2008;Hosokawa et al, 2009;Quan et al, 2008;Satoh et al, 2010), as well as nearly every gene involved in the formation or transfer of N-linked glycans ( Figs. 4A and B).…”
mentioning
confidence: 99%